Employment problems of monocities in East Kazakhstan region (Journal of Economic Research & Business Administration, 2016)
This article describes the problems of employment in the monocities of East Kazakhstan region. With the transition to market relations in Kazakhstan the problem of unemploy ment in monocities have become highly relevant; its powerful influence on migration and reproduction of the population has led to a reduction in the workforce. Four monocities like Ridder, Zyryanovsk, Kurchatov and Serebryansk in the East Kazakhstan region have had poor socio-economic status, it was associated with a lack of jobs, low cash incomes, and as a result, high level of unemployment and the share of self-employed persons, which was the main reason for migration outflow and trend aging of the population. Employment prob lems of monocities in East Kazakhstan region is the same as the other standard monocities of Kazakhstan, these are: an acute shortage of labor resources and qualified personnel, in monocities, and in other sectors of the economy, difficult working conditions in monocities with low wages, high risk of marginalization due the shortage of labor, etc.
Keywords: monocities development program; employment; labor; migration outflow; EKRmonocities; comprehensive development plan.